(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-healthcare hospital workers, including security personnel, attenders, housekeeping staff, sweepers, and solid waste management workers, constitute an indispensable yet frequently neglected segment of the hospital workforce. Despite their critical role in sustaining hospital operations, their occupational health and quality of life (QoL) remain inadequately studied, particularly in resource-limited tertiary care settings. Objectives: To assess health-related quality of life (HRQoL) among non-healthcare hospital workers using the EQ-5D-3L instrument and EQ Visual Analogue Scale (EQ-VAS), and to examine associations between HRQoL and sociodemographic variables including age, sex, income, and occupational category. Materials and Methods: A cross-sectional observational study was conducted over four months in a tertiary care teaching hospital. A total of 128 non-healthcare workers were recruited using convenience sampling. HRQoL was assessed using the validated EQ-5D-3L questionnaire and EQ-VAS. Data were analyzed using IBM SPSS v26.0, employing descriptive statistics, independent samples t-test, Chi-square test, Kruskal–Wallis test, Mann–Whitney U test, and Spearman correlation. Results: The mean EQ-VAS score was 73.6 ± 16.0. Pain/discomfort (53.9%) and anxiety/depression (30.5%) were the most prevalent impaired EQ-5D dimensions. Older age and lower income were significantly associated with poorer HRQoL (p < 0.05). Female participants reported a significantly higher prevalence of health-related problems compared to males (81.1% vs. 50.0%, p = 0.006). Conclusion: Non-healthcare hospital workers carry a substantial burden of health-related impairment. Targeted occupational health interventions, ergonomic support, mental health services, and institutional welfare programs are urgently needed. This study contributes to the evidence base for policy-level attention toward this vulnerable workforce.